Evaluasi dan Perbaikan Desain Antarmuka Pengguna Menggunakan Metode Usability Testing dan Human-Centered Design (Studi Kasus: DPAD Malang Mobile Library) - Jerry Deska Perdana; Hanifah Muslimah Az-zahra; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Malang Library is a regional library in Malang City. It already has its own application that is integrated with the physical library named DPAD Malang Mobile Library. When using the application, user has some problems. One example, when user press the back button on their smartphone, the application close itself instead of going back to previous page. Writer also did preliminary evaluation using UEQ method to 20 library members. Result shows that DPAD Malang Mobile Library has a â€œbadâ€ score on all scale of UEQ except for perspicuity with a â€œbelow averageâ€ score. Also, Malang Library still have not upload the application to Google Play because they want to polish the application on the user interface side. If the application is uploaded without polishing the user interface, it will cause negative experience to the user. Because of that, writer did an evaluation and fixing the application using Human-Centered Design approach and Usability Testing method for evaluation. Steps on this research are understand and specify the context of use with observation and interview, preliminary evaluation using Usability Testing method and specifying the user requirements, produce design solution with Material Design Guidelines, evaluating the design using Usability Testing method, and fixing the design solution with Material Design Guidelines.